Laurelcherry Smoky Moth, Neoprocris floridana Tarmann 1984 (Insecta: Lepidoptera: Zygaenoidea: Zygaenidae: Procridinae) - Donald W. Hall (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 12-page fact sheet that discusses the laurelcherry smoky moth was written by Donald W. Hall, and published by the UF Entomology and Nematology Department, October 2015.